Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2007
DOI: 10.1111/j.1600-6143.2007.02006.x
|View full text |Cite
|
Sign up to set email alerts
|

Proteinuria After Kidney Transplantation, Relationship to Allograft Histology and Survival

Abstract: Proteinuria is associated with reduced kidney allograft survival. Herein we assessed the association between proteinuria, graft histology and survival. The cohort included 613 kidney allograft recipients who had proteinuria (measured) and surveillance biopsies at 1-year posttransplant. Proteinuria >150 mg/day was detected in 276 patients (45%) and in 182 of these, proteinuria was below 500. In >84% of patients even low levels of proteinuria were associated with albuminuria. Proteinuria was associated with the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

23
161
2
5

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 179 publications
(191 citation statements)
references
References 32 publications
23
161
2
5
Order By: Relevance
“…In a recent study from our center, 45% of transplant recipients in general were found to have proteinuria (4150 mg/day), including 7% with proteinuria 41.5 g/day. 13 Therefore, C1q deposition may not be responsible for proteinuria in our patients. The milder clinical and pathological features associated with C1q deposition in the allograft compared with the native kidney are possibly due to the disease detection at early stages by protocol biopsies, the therapeutic effects of the maintenance immunosuppression regimens administered to prevent graft rejection, and/or the hemodynamic effects of calcineurin inhibitors.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…In a recent study from our center, 45% of transplant recipients in general were found to have proteinuria (4150 mg/day), including 7% with proteinuria 41.5 g/day. 13 Therefore, C1q deposition may not be responsible for proteinuria in our patients. The milder clinical and pathological features associated with C1q deposition in the allograft compared with the native kidney are possibly due to the disease detection at early stages by protocol biopsies, the therapeutic effects of the maintenance immunosuppression regimens administered to prevent graft rejection, and/or the hemodynamic effects of calcineurin inhibitors.…”
Section: Discussionmentioning
confidence: 66%
“…This recommendation is based on recent data indicating that proteinuria after kidney transplantation, even at low levels (o500 mg/day), is associated with reduced graft survival, independent of glomerular pathology, graft function, and acute rejection. 13,15 In the recent study by Vizjak et al, 6 of 72 cases of C1q nephropathy in the native kidney, 37.5% of patients had underlying infections, most commonly upper respiratory tract infection. Furthermore, the single previously reported patient with de novo 'C1q nephropathy' in the renal allograft had concurrent BK polyoma interstitial nephritis.…”
Section: Clinical Featuresmentioning
confidence: 99%
“…In studies involving adult populations which used a very liberal threshold of 2-3 g/day, prevalence was only 10-15 % [5,7]. In contrast, studies that used a threshold similar to that used for non-transplanted patients (0.15-0.25 g/day) revealed proteinuria in 31-45 % of patients [4,11].…”
Section: Prevalence Of Post-transplant Proteinuria and Methods For Itmentioning
confidence: 97%
“…The prevalence of proteinuria reported in different studies on adult and pediatric populations varies considerable, from 11 to 82 % [4][5][6][7][8][9][10][11][12][13]. The main reason for this wide variation in prevalence of proteinuria is the different threshold used in these studies to define proteinuria.…”
Section: Prevalence Of Post-transplant Proteinuria and Methods For Itmentioning
confidence: 99%
“…Da mesma forma, a presença de proteinúria é um fator de risco associado à sobrevida do paciente e do enxerto em receptores de transplante renal. 35 A média da concentração de proteína em amostra isolada de urina foi de 0,52 g/dL no primeiro ano de transplante, com aumento gradual (58%) até 0,82 g/dL no quinto ano de transplante, sendo que nenhum paciente apresentou valores de proteinúria que ultrapassassem 1 g/L. Não podemos determinar se esse grau e incremento na proteinúria é consequência direta do uso de SRL, do desenvolvimento da disfunção crônica do enxerto, recorrência ou glomerulopatia "de novo" ou, o que é mais provável, uma combinação desses fatores.…”
Section: Discussionunclassified